Pendampingan tentang Pemilihan Makanan Sehat kepada Anak Asuh Rumah Singgah - Purwaningtyas Kusumaningsih; Diah Widiawati Retnoningtyas; I Made Gde Sudyadnyana Sandhika (LPPM Universitas Flores, 2021)
Knowledge in healthy foods selection needs to be taught to childrens and adolesncent as the next generation for Indonesia. It because foods that they consume will give many impact to their health, physical growth, mentally and intelligent. Many factors can influence the children and adolescent in selecting helathy food, such as parenting, environment, economic, pshycology and education. Education as the last factor was choosen as a method to transfer knowledge about selecting a helathy foods in this community service activities. Improving foster knowledges in selecting healthy foods, which located in Klungkung district had purposed to give solution to the foster in knowing healthy foods and giving understanding what were the impact of safe and healthy foods to them. In order they will able to review of negative or positive impact before they consume foods. The success in this community service activities were from analyzed scored of pre and post test by Wilcoxon analysis in SPSS 16. The obtained result showed if p-value was less then 0.05 (p=0.001), it means that the foster could received the subjects clearly by lecture and playing methods. In discussion between team and the foster, when they choose and consume healthy foods will give advantages and will support them in reacing academic, sport and other achievments. Females foster understand if they consumed healthy foods they will able to maintains their weight and avoid anemia. Males foster also know they will built good stamina to do many activities. In conclusion education about selecting healthy foods need sustainable action from people around the children and adolescent. In case it will built their good habits and behavior in ways to choose healthy foods in whole their life. A demonstration in processing healthy foods can be a skill and provision to introduce the healthy foods directly to them.